The role conflict among Female teachers and employees of Raparin University (Raparin Journal of Humanities (RJH), 2024)
The aim of this study was to determine the level of role conflict among female teachers and employees of Raperin University in general and according to the variables (marital status, educational level, and years of service). The research community consists of all female teachers and employees in Raperin University, and the sample consists of (114) teachers and employees. The research tool consists of a role conflict scale consisting of 36 items prepared by the researchers. The statistical methods used were: one-sample t test and (ANOVA). The results showed that role conflict was low in the sample. According to the variables, the marital status variable did not show significant differences between the single and married groups, but there were significant differences according to education and years of service.